1993
DOI: 10.1007/bf01299888
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection in asymptomatic anti-HIV1 negative pregnant women and their children

Abstract: The prevalence of hepatitis C virus (HCV) infection was studied prospectively in pregnant women in France and their children by detection of anti-HCV with second-generation ELISA (ELISA2). In ELISA2-positive women, anti-HCV was detected with second- and third-generation RIBA (RIBA2 and RIBA3) and serum HCV RNA was detected with PCR. Among 670 women, anti-HIV1-negative, 26 (3.9%) were positive with ELISA2. RIBA2 was positive in 13 and HCV RNA was found in 10. Ten ELISA2-positive women had a further evaluation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 11 publications
3
15
0
1
Order By: Relevance
“…Furthermore, the presence of HCV-RNA in these mothers was well associated with positivity of RIBA-2. Similar results were also found in a previous study of anti-HCV positive pregnant women [12]. Our resuits indicated that most mothers confirmed to be anti-HCV-positive by RIBA-2 were HCV carriers, while ELISA-2 positivity with a low titre (ODI <2.0) might represent a false-positive reaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the presence of HCV-RNA in these mothers was well associated with positivity of RIBA-2. Similar results were also found in a previous study of anti-HCV positive pregnant women [12]. Our resuits indicated that most mothers confirmed to be anti-HCV-positive by RIBA-2 were HCV carriers, while ELISA-2 positivity with a low titre (ODI <2.0) might represent a false-positive reaction.…”
Section: Discussionsupporting
confidence: 91%
“…We found 3 cases of mother-to-infant transmission among the 31 (9.7%) in the present study. This rate of the transmission was somewhat higher than that found in similar reports in which infants born to anti-HCV positive and anti-HIV negative mothers were evaluated prospectively [11,12,21,27]. Some investigators have indicated a high level of viraemia in mothers to be a possible risk factor of HCV transmission [tl, 16].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…La prévalence d'anticorps anti-VHC chez les femmes enceintes est identique à celle de la population générale, et d'environ 1 % (0,3 à 3,9 %) [1][2][3]. Parmi elles, 70 à 80 % sont virémiques (ARN-VHC positives) [4,5].…”
unclassified